Google Books Ngram Viewer in Socio-Cultural Research - Zięba, Anna (Research in Language, 2018)
The objective of this paper is to verify if Google Books Ngram Viewer, a new tool working on a database of 361 billion words in English, and enabling quick recovery of data on word frequency in a diachronic perspective, is indeed valuable to socio-cultural research as suggested by its creators (Michel et al. 2010), i.e. the Cultural Observatory, Harvard University, Encyclopaedia Britannica, the American Heritage Dictionary, and Google. In the paper we introduce a study performed by Greenfield (2013), who applies the program to her Ecological Analysis, and contrast the findings with a study based on similar premises, in which we follow the trends in changes in word frequency throughout the 19th and 20th centuries to observe if these changes correspond to one of the major socio-cultural transformations that took place in the studied period, i.e. mediatization. The results of this study open a discussion on the usefulness of the program in socio-cultural research.